The fifth edition of the WHO-Classification: what is new for cutaneous lymphomas? CME article - Melchers, Susanne; Albrecht, Jana Dorothea; Kempf, Werner; Nicolay, Jan Peter (Journal der Deutschen Dermatologischen Gesellschaft, 2024)
The recently published 5th edition of the “World Health Organization classification of hematolymphoid tumors: lymphoid neoplasms” provides a hierarchical reorganization. In general, new (definitive) entities as well as tumor-like lesions were included. Primary cutaneous B-cell lymphomas (CBCL) received a thorough review. A new class/family of cutaneous follicle center lymphomas was defined. Primary cutaneous marginal zone lymphoma is now presented as a separate entity independent from extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue. In primary cutaneous T-cell lymphoma, former provisional entities were upgraded to definite entities. Sézary Syndrome was sorted into the class/family of mature T-cell and NK-cell leukemias. Additionally, a newly formed entity of primary cutaneous peripheral T-cell lymphoma, NOS was created for CTCL entities that do not fit into the already described CTCL entities. The increasing importance of genomic and molecular data has already been recognized in classifying leukemias and systemic lymphomas. However, in PCL the genomic landscape has not yet been fully described and validated. Therefore, future research is necessary to describe the genomic and molecular mechanisms underlying the disease entities more clearly. This would both meet a diagnostic need and valuably contribute to future classification schemes.
Erstmals veröffentlicht: 01. August 2024
Gesehen am 05.11.2024